Resolution of Bitot's spots following mega-dose vitamin A supplementation in children between 1 and 5 years of age. Issue 7 (17th June 2013) - Kapil, Umesh; Dwivedi, Shraddha; Sachdev, Harshpal S; Dwivedi, SN; Pandey, RM; Hirdyani, Harsha; Upadhyay, Ashish
Abstract Objective The prevalence of Bitot's spots (BS) is often used to quantify vitamin A deficiency burden in India, both before and after mega-dose vitamin A supplementation (MVAS) programmes. However, the proportion of BS cured following this intervention is unclear in contemporary times. The current study evaluated the responsiveness of BS over 1 year to MVAS administered as per the national programme in rural India. Design Prospective, community-based, 1-year follow-up of a cohort. Setting Rural Uttar Pradesh, India. Subjects Two hundred and sixty-two children with BS, aged between 1 and 5 years, administered 60 mg (retinol equivalent) of vitamin A on diagnosis and after 1 month. Cure or resolution was defined if there was no discernible BS in either eye. Results During 1 year, only three children were lost to follow-up. At 6 months of follow-up (MVAS at baseline and 1 month later), 51·1 (95% CI 45·3, 57·3) % were classified as cured. The corresponding figure at 1 year (additional MVAS at 6 months) was 59·9 (95% CI 54·1, 65·9) %. Among those cured at 6 months, about half and three-quarters had resolved at 2 and 3 months, respectively. Apart from male gender, there were no significant sociodemographic or clinical predictors of response. Conclusions Substantial non-response to MVAS at 6 months (49%) and 1 year (40%) of follow-up suggests that presently in the Indian subcontinent, BS is a relatively crude indicator of severe current vitamin A deficiency. For programmatic decisions and evaluation, the public health burden of vitamin A deficiency should not be assessed solely through BS.